Investigating Discourses of Indigeneity and Taino Survival in Jamaica - Shenhat Haile (Caribbean Studies Students' Union, 2022)
In Jamaica, the longstanding notion of indigenous extinction through colonial violence and subsequent intermixing with enslaved Africans has led to widespread debate on the island regarding the legitimacy of Taíno survival. Colonial narratives attesting to the absolute decimation of original inhabitants throughout the Caribbean region have arguably created stagnant understandings of indigeneity in Jamaica into the 21st century. This paper seeks to investigate complex conceptualizations of indigeneity on the island and explore the ways in which the myth of extinction has persisted into the post-colonial period, along with the challenges related to the reconstruction of Taíno histories in Jamaica.